2017
DOI: 10.22158/rhs.v2n1p12
|View full text |Cite
|
Sign up to set email alerts
|

Employment Status, Anxiety and Depression in a Municipal Context

Abstract: 7.76 (5.97-9.75) and 4.67 (3.60-5.74)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Females developed more anxious and depressive symptoms after vaccination than males, and the employed developed more anxiety and depressive symptoms than their unemployed counterparts. This finding is consistent with that before the pandemic [ 7 , 8 , 9 ]. However, few studies have explored the association between demographics and mental distress after vaccination.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Females developed more anxious and depressive symptoms after vaccination than males, and the employed developed more anxiety and depressive symptoms than their unemployed counterparts. This finding is consistent with that before the pandemic [ 7 , 8 , 9 ]. However, few studies have explored the association between demographics and mental distress after vaccination.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies indicated that mental health is associated with socio-demographic factors such as gender, education level, and employment status [ 2 , 3 , 4 , 5 , 6 ]. For instance, females were reported to relate to a higher level of anxiety and depression than males [ 7 , 8 , 9 ]. Unemployment status was also reported to correlate to worse mental health [ 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Approximately 750,000 prostate cancer survivors in the United States are depressed. 25 The authors of the conceptual model suggested that sociodemographic characteristics (eg, race, unemployment, and low income), [26][27][28][29][30][31][32] lifestyle factors (eg, a lack of exercise), 33,34 acute and chronic burdens (eg, treatment decisional regret), and interpersonal situations affect a person's susceptibility to stress vulnerabilities that often precede depression. The goal of this study was to describe the prevalence and predictors of probable depression in prostate cancer survivors (we use the Cancer October 1, 2019 word probable because of our identifying strategy; more details are given later).…”
Section: Introductionmentioning
confidence: 99%
“…22 The analytic approach was informed by Kinser and Lyon's conceptual model for individual stress vulnerability, depression, and health outcomes. 25 The authors of the conceptual model suggested that sociodemographic characteristics (eg, race, unemployment, and low income), [26][27][28][29][30][31][32] lifestyle factors (eg, a lack of exercise), 33,34 acute and chronic burdens (eg, treatment decisional regret), and interpersonal situations affect a person's susceptibility to stress vulnerabilities that often precede depression. 25 After reviewing evidence on stress vulnerabilities in other patient populations, we hypothesized that sociodemographic characteristics such as age, African American race, low education, rural residence, being unmarried, unemployment, and low income were positively associated with probable depression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to type of job, age, sex, level of education and job status are known occupational risk factors for mental health problems [13]. In a systematic review of epidemiological research, type of job, age, sex, level of education and job status were associated with both depressive state and anxiety [14]. Thus, type of job and age, sex, level of education and job status may be interrelated in their effect on mental health and all factors should be considered simultaneously.…”
Section: Introductionmentioning
confidence: 99%